Phase separation of gas–liquid two‐phase stratified and plug flows in multitube T‐junction separators. Issue 6 (5th November 2016) - Yang, Limin; Wang, Jiahao; Zhao, Zhenying; Xu, Shengbo; Azzopardi, Barry J; Wang, Hong
Abstract : Using air and water as the working fluids, phase separation phenomena for stratified and plug flows at inlet were investigated experimentally, at a simple T‐junction and specifically designed multitube T‐junction separators with two or three layers. The results show that for these two flow patterns the separation efficiency of the two phases for any multitube T‐junction separator is much higher than that of the simple T‐junction. Increasing the number of connecting tubes in the multitube T‐junction separator can increase the separation efficiency. Generally, for stratified flow, complete separation of the two phases can be achieved by the two‐layer multitube T‐junction separator with five or more connecting tubes and by the three‐layer separator; increasing the gas flow rate, the liquid flow rate, or the mixture velocity under plug flow is detrimental to phase separation with a drop in peak separation efficiency. © 2016 American Institute of Chemical Engineers AIChE J, 63: 2285–2292, 2017